A new approach in banking branchless (digital) banking and customer acquisition case study of kuveytturk bank - DAĞIDIR ÇAKAN, CANAN (My University, 2022)
Technology, which is constantly evolving, has had an impact on the banking industry, making it innovative and providing new perspectives to banking. The provision of financial services without or with a minimal number of branches is known as branchless (digital) banking. With the insight that banking will endure forever, but that bank offices will no longer be required, various approaches for customer acquisition have been developed. In this study, first of all, branchless (digital) banking and its advantages are explained and customer acquisition methods in branchless banking which are opening an account via video call over the mobile branch, opening an account by applying for an account from the internet branch and signing a contract via a courier, and opening an account via an XTM (Extreme Transaction Machine) device were examined. Kuveyt Turk Participation Bank's sample channels, which utilise these methodologies, were examined. As a result, it has been determined that the bank's operational efficiency has increased thanks to branchless (digital) banking and it has made significant contributions to its sustainability goals. While using these methods, it is anticipated that the number of personnel needed will decrease due to the shortening of the processing times, while the satisfaction of the bank's customers will increase.

Günden güne gelişen teknoloji bankacılık sektörünü de etkileyerek onu yeni bir hale sokmuş ve bankacılığa yeni anlayışlar getirmiştir. Şubesiz (dijital) bankacılık, bankacılık hizmetlerinin şubesiz veya az sayıda şube ile verilmesidir. Bankacılığın sonsuza kadar süreceği, ancak banka şubelerine ihtiyaç duyulmayacağı öngörüsü ile bu anlayışta müşteri edinimi için farklı yöntemler oluşturulmuştur. Bu çalışmada öncelikle şubesiz(dijital) bankacılık ve avantajları anlatılmış olup şubesiz bankacılıkta müşteri edinimi yöntemleri olan mobil şube üzerinden görüntülü görüşme ile hesap açılışı, internet şubesinden hesap açılışı başvurusunda bulunup kurye aracılığıyla sözleşme imzalayarak hesap açılışı ve XTM (Extreme Transaction Machine) cihazı üzerinden hesap açılışı yöntemleri incelenmiştir. Şubesiz (dijital) banka örneği olan Kuveyt Türk Katılım Bankası’ nın örnek kanalları analiz edilmiştir. Sonuç olarak, şubesiz (dijital) bankacılık sayesinde bankanın operasyonel verimliliğin arttığı ve sürdürülebilirlik hedeflerine önemli katkıları olduğu tespit edilmiştir. Bu yöntemler kullanılırken işlem sürelerinin kısalması sebebiyle ihtiyaç duyulan personel sayısı düşerken, banka müşterilerinin memnuniyetinin artacağı da öngörülmektedir.
Bankacılıkta yeni anlayış şubesiz (dijital) bankacılık ve müşteri edinimi: Kuveyt Türk Bankası vaka çalışması
Keywords: Şubesiz(Dijital) Bankacılık; Müşteri Edinimi; Uzaktan Müşteri Edinimi; Ekstrem İşlem Makinesi; Kuveyt Türk Katılım Bankası; : Branchless (Digital) Banking; Customer Acquisition; Digital Onboarding; Extreme Transaction Machine; Kuveyt Turk Participation Bank